Scaling-up of membraneless microbial electrolysis cells (MECs) for domestic wastewater treatment: Bottlenecks and limitations. (March 2015) - Escapa, A.; San-Martín, M.I.; Mateos, R.; Morán, A.
Graphical abstract: Highlights: Two twin units of a modular pilot scale membraneless MEC were studied. Identical inoculation processes resulted in quite different MEC performances. Only medium strength dWW succeeded in producing hydrogen. Hydrogen recycling threatens both energy efficiency and the quality of the effluent. The cathode design and start-up process are critical issues in MEC performance. Abstract: Microbial electrolysis cells (MECs) have the potential to become a sustainable domestic wastewater (dWW) treatment system. However, new scale-up experiences are required to gain knowledge of critical issues in MEC designs. In this study we assess the ability of two twin membraneless MEC units (that are part of a modular pilot-scale MEC) to treat dWW. Batch tests yielded COD removal efficiencies as high as 92%, with most of the hydrogen (>80% of the total production) being produced during the first 48 h. During the continuous tests, MECs performance deteriorated significantly (energy consumption was relatively high and COD removal efficiencies fell below 10% in many cases), which was attributed to an inadequate configuration of the anodic chamber, insufficient mixing inside this chamber, inefficient hydrogen management on the cathode side and finally to dWW in itself. Some alternatives to the current design are suggested.